2020
DOI: 10.3390/ijerph17124535
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Testing and Prediction Equations in Adult Population from Maputo, Mozambique

Abstract: Background: Local spirometric prediction equations are of great importance for interpreting lung function results and deciding on the management strategies for respiratory patients, yet available data from African countries are scarce. The aim of this study was to collect lung function data using spirometry in healthy adults living in Maputo, Mozambique and to derive first spirometric prediction equations for this population. Methods: We applied a cross-sectional study design. Participants, who met the inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…We report mean spirometry test values in pregnant women which are lower than the means reported in Brazilians (20). The non-pregnant means of FVC, FEV1, PEF and their % predicted in this study are comparable to values reported from other studies done in Tanzania (29), Rwanda (30) and Mozambique (31). Our values were slightly higher than the other studies because of the age difference as the mean age of non-pregnant women was less than 30 years in this while it was more than 35 in the other studies.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We report mean spirometry test values in pregnant women which are lower than the means reported in Brazilians (20). The non-pregnant means of FVC, FEV1, PEF and their % predicted in this study are comparable to values reported from other studies done in Tanzania (29), Rwanda (30) and Mozambique (31). Our values were slightly higher than the other studies because of the age difference as the mean age of non-pregnant women was less than 30 years in this while it was more than 35 in the other studies.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, there is a lack of reference values for spirometry parameters and their associated factors among pregnant in Sub Saharan Africa including Tanzania. Few studies available only involved non-pregnant African women (29)(30)(31). Therefore, the test results among pregnant women are compared against the general population reference values.…”
mentioning
confidence: 99%
“…Apart from differences in study design, there could be other sources for the heterogeneity observed in our data. For instance, the use of inadequate reference standards or diagnostic thresholds, especially for study populations that are not represented by common standards like the Global Lung Function Initiative, could lead to over- or under-reporting of lung impairment [ 13 , 86 , 87 ]. In addition, there was an indication for a systematic under-reporting of restriction or mixed impairment types within the reviewed studies.…”
Section: Discussionmentioning
confidence: 99%
“…But this amount was estimated at 10% in Mozambique's reference population (Southeast Africa (. 23 , also the LLNs of FEV 1 /FVC were less than 0.70 in men above 56 years of age and women above years of age in Chinese aged 4-80 years. 1 Concerning the high prevalence in men over 70 years of age, this may be due to the low sample size in this age group (16 people).…”
Section: Discussionmentioning
confidence: 74%